(untitled) (Journal of the College of Basic Education, 2023)
The present research aims to: Realizing the effectiveness of an experimental program based on conscious discipline skills in the performance of students applied at experimental of Arabic language, colleges of education is known. To achieve this, the researcher followed the descriptive approach in the procedures of building the training program through three main stages: planning, implementation and evaluation. The researcher specified the justifications for building the training program, its philosophy and intellectual premises, its objectives, both public and private. The researcher, moreover, organized the training content and identified training methods and means consistent with the objectives of the training program. The researcher followed the quasi-experimental approach in the procedures of identifying the effectiveness of the training program on the performance of students applied at Departments of Arabic Language, Colleges of Education. In order to achieve